Effective of high-intensity interval training and moderate-intensity continuous training on body composition, glycolipid metabolism, and cardiopulmonary function in patients with pre-diabetes: a randomized controlled trial - Chen, Xinbei; Wu, Lijuan; Zheng, Yan; Ni, Xuling; Zhuang, Xiaojin; Chen, Liming; Hu, Qiaoling; Zou, Chunyan; Yin, Lianhua (Frontiers in Endocrinology, 2025)
AimsThe aim of this study is to compare the effectiveness of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on body composition, cardiovascular function, glycolipid metabolism, and cardiopulmonary function in patients with pre-diabetes.MethodsSeventy-one participants were randomly assigned to the HIIT (10 × 1-min at 75%–90% HRpeak, intersperse with 1-min active recovery at 50% HRpeak) or MICT (50 min at 55%–70% HRpeak) for a 12-week (three times per week) program. The outcome measured was the change in body composition, cardiovascular index, glycolipid metabolism, and cardiopulmonary. The trial was registered on the Clinical Trial Registry (ChiCTR1900026905).ResultsThe body mass index decreased in the HIIT (P = 0.016) and MICT (P = 0.021) groups. The participants in the MICT group had a significantly decreased in visceral adipose area (P = 0.043) and body fat rate (P = 0.030) after training, compared with the HIIT group. Analysis of systolic blood pressure revealed statistical difference in the HIIT and MICT interventions (P < 0.001), but there was not statistical difference between groups (P = 0.398). MICT was better than HIIT in reducing diastolic blood pressure (P = 0.011). The significant effect of fasting blood glucose, 2-h glucose, and glycated hemoglobin (HbA1c) showed an obvious descent in the HIIT and MICT groups (P < 0.001). Regarding the blood lipid, triglyceride decreased significantly more in the MICT group than that in the HIIT group (P = 0.006). VO2peak increased in both the HIIT and MICT groups, but there was no significant between-group difference (P = 0.647).ConclusionHIIT and MICT significantly improved blood glucose and aerobic capacity in patients with pre-diabetes. However, MICT was superior to HIIT in terms of visceral fat, lipids, and diastolic blood pressure.Clinical Trial Registrationhttps://www.chictr.org.cn/, identifier ChiCTR1900026905.